2022
DOI: 10.1002/app.52477
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane adhesives from castor oil and modified lignin via reaction with propylene carbonate

Abstract: Over the last several years, lignin hydroxypropylation with propylene oxide (PO) has been used as the main strategy to overcome lignin limitations, such as its low reactivity, poor dispersion, and high stiffness, in the context of polyurethane (PU) synthesis. However, PO is a flammable, toxic, and carcinogenic compound. Propylene carbonate (PC), a compound with low toxicity and biodegradability, has emerged as a feasible alternative to PO. Although this compound has potential for use in syntheses, lignin hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 59 publications
2
14
0
Order By: Relevance
“…After approximately 0.20 h, in stage II, a reduction of the slope of the N Mean vs time curves was observed, indicating a significant decrease in the reaction rate of BPUP_30KL and BPUP_30HKL_PO prepolymerization. This behavior is a consequence of two factors: (a) the decrease in reagent concentrations after their consumption and (b) the decrease in molecular mobility due to a molecular weight increase, which slows further diffusion of the reactants. , Despite showing similar trends, the system containing HKL_PO displayed higher reaction rates throughout stage II than the one containing KL. This result suggests that the modified lignin has a higher reactivity compared to the unmodified one, which is in agreement with the FTIR analysis (Figure ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…After approximately 0.20 h, in stage II, a reduction of the slope of the N Mean vs time curves was observed, indicating a significant decrease in the reaction rate of BPUP_30KL and BPUP_30HKL_PO prepolymerization. This behavior is a consequence of two factors: (a) the decrease in reagent concentrations after their consumption and (b) the decrease in molecular mobility due to a molecular weight increase, which slows further diffusion of the reactants. , Despite showing similar trends, the system containing HKL_PO displayed higher reaction rates throughout stage II than the one containing KL. This result suggests that the modified lignin has a higher reactivity compared to the unmodified one, which is in agreement with the FTIR analysis (Figure ).…”
Section: Resultsmentioning
confidence: 97%
“…First, its use alone, as the only polyol in PU formulations, is disadvantageous because it results in highly brittle materials . For that reason, lignin is frequently blended with other polyols, such as polyethylene glycol (PEG), a conventional petroleum-based polyol, and, in a sustainable approach, vegetable oils, such as castor oil for example. , This second polyol acts as the soft segment in the lignin-based PU formulation. Even with the addition of the second polyol, lignin can only be incorporated up to 30 wt % without deterioration of the PU’s mechanical properties. , Another drawback is the low reactivity of the lignins’ hydroxyl groups against isocyanates, especially aromatic ones, due to steric hindrance .…”
Section: Introductionmentioning
confidence: 99%
“…The superior performance of lignin-based adhesives compared to CPA can be attributed to the following reasons: (1) the aromatic nature of lignin, which contributes to their stiffness [ 40 , 41 ], and (2) the modification of lignin, which yields a polyether with mainly primary OH groups which react promptly with the polyisocyanate. Thus, increasing the crosslinking density of the polymer matrix and subsequently the adhesive strength [ 28 ]. Furthermore, the crude LBP contains residual catalyst and PC-oligomer, which may promote the crosslinking of the polymeric network, as well as enhance the wettability of the surface and convey some flexibility [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Yet, Gouveia et al [ 27 ] prepared lignin-based PU adhesives from kraft lignin oxyalkylated with PO under different conditions. In a similar manner, the same group prepared lignin-based PU adhesives by mixing castor oil with up to 30 % of LBP oxyalkylated with PC [ 28 ]. So far, to the best of our knowledge, these are the only studies that reported the use of oxyalkylated lignin with cyclic carbonate to produce PU adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…Gouveia et al [ 149 ] prepared PU adhesives for wood bonding from kraft lignin oxyalkylated under mild conditions with PO. Recently, the same group prepared PU adhesives by mixing castor oil with up to 30% of LBPs oxyalkylated with PC, where the use of LBPs improved the Young’s modulus and adhesion [ 150 ]. So far, this is the only study that has reported the use of lignin oxyalkylated with cyclic carbonate to produce PU adhesives.…”
Section: Lignin As a Building Block To Synthesize Polyurethanesmentioning
confidence: 99%